Institutionalizing transport impact assessment the case of Cotabato City - Rendon, Ma. Clarissa E.
The study is primarily intended to find out how Transport Impact Assessment(TIA) can be institutionalized in a local government unit, The City of Cotabato in particular. To achieve this general objective, the study looked into the factors that might facilitate or hinder the institutionalization of TIA, reviewed existing national and local policies that require TIA for any type of development, and came up with an institutionalization mechanism. Further, the study adopted Transport Impact Assessment rather than Traffic Impact Assessment.The study made use of key informant interview and focus group discussion. Respondents were selected based on their position, involvement in TIA institutionalization and participation to the Local Development Council. The study found out that an enabling ordinance facilitates the institutionalization of TIA while the hindering factors are political support and appreciation on TIA of both the executive and legislative. The best way to institutionalize TIA is to incorporate it as a policy in the Comprehensive Land Use Plan and Zoning Ordinance. The study recognized the knowledge of the local planning office on TIA is essential and eased the process of integrating TIA as a measure to mitigate the impact of new developments on transportation. With TIA being institutionalized thru CLUP and Zoning Ordinance, there is no need to pass for a separate enabling ordinance and enforcement of TIA became the responsibility of the Zoning Administrator. Within the local government system, the study found out the ideal way to require TIA is in the building permit approval process and considering, it is mainstreamed in the Zoning Ordinance, and such shall be required at the level of securing a Locational Clearance as a requirement to building permit and subdivision. The study has established the appropriateness to use Transport Impact Assessment instead of Traffic Impact Assessment since the former is being regarded as a land use measure that affects the environment and helps combat climate change rather than a traffic control policy.
Keywords: Transport impact assessment -- Cotabato City(Philippines); Transportation -- Passenger traffic -- Cotabato City(Philippines) -- Assessment